Presidential Decree-Law No. 25/2014 On Amending Certain Provisions of the Traffic Law Promulgated by Law No. 66/1973 - egypt (2025)
Presidential Decree-Law No. 25 of the year 2014 on amending certain provisions of the traffic law promulgated by law no. 66 of the year 1973 – قرار رئيس جمهورية مصر العربية بالقانون رقم 25 لسنة 2014 بتعديل بعض أحكام قانون المرور الصادر بالقانون رقم 66 لسنة 1973